Evaluation Of Biology Teachers' Knowledge in Sidoarjo Regarding the Concept Of Poliovirus and Wolbachia Infected Mosquitoes - Adrianto, Hebert; Firmanto , Ian Ardhiya; Mellyanawati, Mellyanawati; Bravimasta , Bracovanca Diwayestara; Tantana, Olivia; Ritunga, Imelda (Poltanesa, 2024)
Biology is a dynamic and constantly developing science. The Ministry of Health of the Republic of Indonesia reported nine cases of childhood polio in East Java in January 2024. In addition, the Ministry of Health launched a pilot project to implement Wolbachia-infected mosquitoes as an innovation to control dengue fever in five big cities in Indonesia. This health problem is studied in biology lessons on viruses in senior high school. This paper aims to analyze the knowledge of the concepts of polioviruses and Wolbachia-infected mosquitoes in the biology teacher community in Sidoarjo. The respondents were 43 biology teachers in Sidoarjo. Respondents' prior knowledge was measured by pretest. After the respondent takes the pretest, the respondent gets the concept of the virus. After the material, respondents do a post-test. 11 pretest questions and 11 post-test questions are packaged in Google form. The results showed that all participants participated in the activity from start to finish, taking the pretest, listening to the material, and doing the post-test. The pretest mean score was 40.18, and the post-test mean score was 91.36. The highest pretest score was 81.81. The highest pretest score was 100. A total of 15 teachers (34.88%) were unsure that Wolbachia-infected mosquito was the best solution to reduce disease. Twenty-one respondents (48.83%) agreed mainly with society's concern that the Wolbachia-infected mosquito is dangerous for humans. Respondents' knowledge increased after receiving the concept of the virus